PENENTUAN KOORDINAT GEODETIK TITIK BM PASUT JAWA DARI DATA PENGAMATAN GPS - Herry Risdianto (UNIVERSITAS INDO GLOBAL MANDIRI, 2014)
The purpose of this research was to determine the geodetic coordinates Tidal BM points of Java. Determinationof the coordinates is done by GPS measurements at this points for 3 days. Accuracy of the data processing shownon the value of the standard deviation of latitude (φ), longitude (λ), and ellipsoid height (h). The Results of dataprocessing showed that latitude coordinates has range accuracy from 1.84 x 1.84 x 10-6 sec to 10-6 sec. Longitudecoordinates has range accuracy from 1.85 x 1.94 x 10-6 sec to 10-6 sec. While the ellipsoid height has rangeaccuracy from 9 to 12 cm. Observation point that has the highest accuracy of ellipsoid high is Sunda Kelapa, witha level of accuracy of 9.7 cm, while the observation point that has the lowest of accuracy ellipsoid high is Prigi,with a level of accuracy of 12 cm.